The Potential of Curcumin as Prevention and Alternative Treatment for Helicobacter Pylori Associated Diseases - Prabandari, Anak Agung Sagung Mirah; Sari, Ni Nyoman Shinta Prasista (PT BMW Journal Sejahtera, 2024)
Introduction: Helicobacter pylori (H. pylori) is a pathogenic bacterium found in half of the world's population, causing gastrointestinal problems ranging from gastritis and peptic ulcers to gastric cancer. Current triple therapy treatment for H. pylori faces issues of resistance, side effects, and high cost, necessitating alternative therapies. Studies suggest that curcumin, a compound found in turmeric, may have antibacterial effects against H. pylori. Method: This literature review evaluated the potential of curcumin against H. pylori infection. Relevant articles were systematically searched in PubMed, Scopus, Web of Science, and Google Scholar databases using combinations of keywords including